Peran Kemitraan Petani dengan PT. Sang Hyang Seri Terhadap Peningkatan Pendapatan Petani di Kabupaten Sidrap - Mudatsir, Rasdiana; Syarif, Asriyanti; B, Sumarni (Journal Galung Tropika, 2022)
Sang Hyang Seri collaborates with breeder farmers to produce seeds through a partnership program. Partnership evaluation can be done to see how far the implementation of the partnership between PT. Sang Hyang Seri with partner farmers has been running so that the problems encountered during the implementation of the partnership can be identified. The purpose of this study was to determine the benefits of partnerships between farmers and farmers PT. Sang Hyang Seri, analyze the level of satisfaction of farmers with the partnership program with PT. Sang Hyang Seri, analyze the income level of farmers who are in partnership with PT. Sang Hyang Seri. The results of this study are several of the benefits derived from the farmer partnership with PT. Sang Hyang Seri is through a partnership program, farmers will get assistance with production facilities, market guarantees, the company’s purchase price is higher than the prevailing market price, increased farmer skills, better production quality, and increased farmer income. The level of farmer satisfaction with the partnership program with PT. Sang Hyang Seri is with a Customer Satisfaction Index value of 81.12 which is in the range of 0.81-1.00 which indicates that the consumer satisfaction index is on the "very satisfied" criteria, which means that farmers are very satisfied with the partnership program that they have run together. PT. Sang Hyang Seri. The amount of income obtained by farmers is Rp 13,817,592/people. For the partnership program to continue, the company should improve the procedure for paying harvests to farmers, so that there are no more delays in payments. Both parties should better understand the contents of the cooperation agreement contract so that there will be no more problems in the future.